Three-Dimensional Graphic Innovation Based On Computer-Aided Design (CAD) As A Simulation Of Vishnu Jewelry Design - Febriyanto, Wisnu (Corak, 2022)
One of them is the presence of Computer Aided Design (CAD) based software to be one of the solutions in the world of design. This CAD can help a designer in visualizing and translating his ideas through three-dimensional graphics (360° rotation). CAD-based three-dimensional software has several advantages: starting with precision when drawing the design, as well as providing specifications and elements related to the design ise. This technology is efficient and helpful if used to create jewelry designsThis innovation can save the design flow, besides that the designer can display his ideas as a whole (before prototyping) so that corrections can be made quickly. Modifications can be imposed on the shape, size, material use of the product, and so on. This CAD can also convert "commands" from digital format into mechanical motion commands on a production machine (Computer Aided Manufacture / CAM) so that production can increase both in quality and quantity. A designer becomes the starting point for making products and is also able to provide solutions to the products produced. It would be perfect if a designer was able to operate this graphic application.